Public Speaking Workshop for Female Students of Rooihatul Jannah Islamic Boarding School in Improving Presentation Skills - Kurniawan, Dani; Ifani, Muhammad Zulfi; Trilestari, Linda; Jannah, Azzahrah Miftahul (WASATHON Jurnal Pengabdian Masyarakat, 2024)
This study aims to improve the public speaking skills of female santri of Pondok Pesantren Rooihatul Jannah Sukoharjo through specially designed workshops. This research is motivated by the importance of public speaking skills in various aspects of life, especially in the context of da’wah. The method used in this research is experimental method with qualitative approach. Data collection was done through pre-test, workshop implementation, and post-test. The results showed that the public speaking workshop significantly increased self-confidence, overcame stage fright, and overcame blank material in participants. In addition, participants also gave positive responses to the materials and methods presented. The conclusion of this study is that public speaking workshops can be an effective solution in improving the communication skills of santriwati and make a positive contribution to their self-development.